TEACHER STRATEGIES IN IMPROVING CHILDRENS LITERACY THROUGH ONLINE METHODS IN RA NURUL YAQIN MEDAN - Juli Maini Sitepu; Sunnah Hadisah (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to see how the teacher's strategy in improving children's literacy through online methods. The research method used is descriptive qualitative which uses data collection techniques through observation, interviews, and documentation. The data obtained were tested for validity through data triangulation. The results show that learning using this online method can improve children's literacy, but it is not like the situation when meeting face to face with teachers because face-to-face learning does not have a time limit and is not the same as online learning. Online learning time is very limited for children to learn together. However, this online learning provides a positive thing for children, because children have questions about the technology and media used such as cellphones, laptops, so that it will improve children's literacy.Keywords : Teacher Strategies, Literacy, Online methods